(333) Sudan's ten year plan of economic and social development. - Poduval, R. N. (The Institute Of National Planning., 2018)
there have been close ties, political and economic, between Egypt and Sudan, for over a half century (1898-1956) Sudan was under joint Anglo-Egyptian control the condominium) which ended in 1956 when Sudan became independent state.